2006
DOI: 10.1177/153537020623100907
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Folding, Metal-Binding Mechanisms, and Binding Site Structures in Metallothioneins

Abstract: This minireview specifically focuses on recent studies carried out on structural aspects of metal-free metallothionein (MT), the mechanism of metal binding for copper and arsenic, structural studies using x-ray absorption spectroscopy and molecular mechanics modeling, and speciation studies of a novel cadmium and arsenic binding algal MT. Molecular mechanics-molecular dynamics calculations of apo-MT show that significant secondary structural features are retained by the polypeptide backbone upon sequential rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 39 publications
(33 reference statements)
3
29
0
1
Order By: Relevance
“…Metallothioneins are small, cysteine-rich, approximately 56 amino acid residue proteins involved in chelating metals such as Zn, Cd, copper (Cu), silver, mercury, and arsenic (Duncan et al, 2006). Their exact function is elusive but metallothioneins may function as (i) metal resistance proteins for detoxifying Zn, Cd, and Cu; (ii) reservoirs for the storage of excess Zn and/or Cu than can be mobilized under metal limiting conditions; (iii) metal chaperones that deliver Zn to Zn-dependent proteins; and/or (iv) antioxidants that scavenge oxygen radicals (Palmiter, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Metallothioneins are small, cysteine-rich, approximately 56 amino acid residue proteins involved in chelating metals such as Zn, Cd, copper (Cu), silver, mercury, and arsenic (Duncan et al, 2006). Their exact function is elusive but metallothioneins may function as (i) metal resistance proteins for detoxifying Zn, Cd, and Cu; (ii) reservoirs for the storage of excess Zn and/or Cu than can be mobilized under metal limiting conditions; (iii) metal chaperones that deliver Zn to Zn-dependent proteins; and/or (iv) antioxidants that scavenge oxygen radicals (Palmiter, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that small calcium [5,6], copper [7][8][9] and zinc [10][11][12][13][14] proteins in their largely unstructured apo (metal-free) forms can achieve their natively folded structures upon binding of the metal ions delivered as simple metal salts. Relatively little is known about the relationship between metal uptake and folding of small non-heme iron proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The increased nitrogenase activity in adapted strains, might be due to the development of some defense mechanism for tolerance like secretion of exopolysaccharides for complex formation with metals [25] and extracellular metal binding proteins to act as chelators, mitigating the effects of metals [26,27].…”
Section: Discussionmentioning
confidence: 99%